A foundation for complex oxide electronics -low temperature perovskite epitaxy - Henrik H. Sønsteby (Nature Portfolio, 2020)
Designing complex oxides with appreciable low-temperature synthesis remains a challenge. Here, the authors demonstrate an atomic layer deposition process for LaNiO3 to enable epitaxial thin films on LaAlO3 and SrTiO3 substrates deposited at 225 °C, with no annealing required to achieve good electronic properties.